Growth of churches submitted to different doses of hydrogel and containers - Lira, F. O.; Souza, M. E.; Maia, A. H. (Scientific Electronic Archives, 2019)
The cultivation of rubber trees in Brazil has been established as a sustainable and profitable activity, despite all the challenges, the production of rubber trees grows considerably each year. In order to optimize this production, it is necessary to develop techniques for the production of seedlings that present vigor and quality. Therefore, the objective of this work was to evaluate the growth of rubber tree seedlings submitted to different doses of hydrogel and containers. The work was carried out in the seedling nursery of the State University of Mato Grosso, Campus Nova Xavantina. The dosages used were 0, 1, 2, 3 and 4g and the containers were polyethylene bags in dimensions 20x30 and 25x35 cm. To evaluate the effect of the treatments on the growth of the rubber tree seedlings the following variables were measured at 90 days after sowing: Height (cm), stem diameter (mm), H / D ratio, number of triphophils, root length), Dry matter of the leaves (g), dry matter of the stem (g), dry matter root (g). The experimental design was a randomized complete block (DBC) in a 2x5 factorial scheme, two containers and five hydrogel doses, with six replicates for each treatment. From the results obtained in the present work it can be concluded that the dosage of 1g.L-1 of hydrogel and the container 25x35 cm were the most suitable treatments for the initial development of the rubber tree seedlings.